Lateralization of observational fear learning at the cortical but not thalamic level in mice - Kim, Sangwoo; Matyas, Ferenc; Lee, Sukchan; Acsady, Laszlo; Shin, Hee-Sup (NATL ACAD SCIENCES, 2012)
Major cognitive and emotional faculties are dominantly lateralized in the human cerebral cortex. The mechanism of this lateralization has remained elusive owing to the inaccessibility of human brains to many experimental manipulations. In this study we demonstrate the hemispheric lateralization of observational fear learning in mice. Using unilateral inactivation as well as electrical stimulation of the anterior cingulate cortex (ACC), we show that observational fear learning is controlled by the right but not the left ACC. In contrast to the cortex, inactivation of either left or right thalamic nuclei, both of which are in reciprocal connection to ACC, induced similar impairment of this behavior. The data suggest that lateralization of negative emotions is an evolutionarily conserved trait and mainly involves cortical operations. Lateralization of the observational fear learning behavior in a rodentmodelwill allow detailed analysis of cortical asymmetry in cognitive functions.
Keywords: SUBTHALAMIC NUCLEUS; PREFRONTAL CORTEX; STIMULATION; BRAIN; RATS; AMYGDALA; EMOTION; SYSTEMS; PAIN; PROJECTIONS